Efeitos da rotatividade de treinadores sobre o desempenho das equipes de futebol no Brasil - Azevedo, Caio Oliveira (2019)
This studies aims to evaluate the consequences of in-season changes of head-coach on the performance of first division teams of the Brazilian Football Championship. Data from nine seasons (2009 to 2017) were used, with turn-by-turn team result indicators, contextual variables extracted from game overviews and bookmaker information. To evaluate managerial turnover on performance indicators with different degrees of maturation, matching methods were combined with differences in differences estimators. From the estimates obtained, improvement in several measures of performance after the substitution of coach was noticed, considering the game following the change (very short term). However, this effect turns out to be statistically insignificant, when analyzed over a greater maturity of time, or over a larger number of games after the change. Thus, it turns out that the change of coach does not show itself as an effective strategy to improve results, since it is not able to substantively change the performance indicators of the club in the championship.